Incomplete resection increases the risk of local recurrence and negatively affects functional outcome in patients with tenosynovial giant cell tumor of the hindfoot. Issue 7 (October 2020) - Tsukamoto, Shinji; Zucchini, Riccardo; Staals, Eric L.; Mavrogenis, Andreas F.; Akahane, Manabu; Palmerini, Emanuela; Errani, Costantino; Tanaka, Yasuhito
Highlights: Macroscopically incomplete resection increased local recurrence in patients with tenosynovial giant cell tumor of the hindfoot. Incomplete resection status significantly decreased Musculoskeletal Tumor Society score and negatively affected functional outcome. Pathological synovial tissue should be removed as completely as possible to prevent local recurrence and preserve the postoperative function. If the tumor is limited to the intra-articular synovium of tibiotalar joint, complete resection is possible using arthroscopic synovectomy. Abstract: Background: Diffuse tenosynovial giant cell tumors (TGCT) are more likely to occur in the hindfoot and tend to recur after surgical excision. We performed a pooled analysis of hindfoot TGCT cases to identify factors associated with local recurrence and functional outcomes. Methods: We retrospectively reviewed medical records of 33 patients diagnosed with TGCT (15, localized cases; 18 diffused cases) of the hindfoot between 1998 and 2017. Median follow-up was 32 months. Multivariable Cox proportional hazards regression analysis was conducted to estimate the hazard ratios for risk factors for local failure. Generalized linear regression models were used to assess whether resection status, tumor size, tumor type or bone involvement correlated with the Musculoskeletal Tumor Society (MSTS) score. Results: Local failure was reported in 30% (10/33) patients. Multivariable analysis showed that macroscopically incomplete resection was the only independent prognostic factor for poor local failure-free survival ( P = .001). Incomplete resection significantly decreased MSTS score and negatively affected functional outcome ( P = .047). Conclusions: Incomplete resection increases the risk of local recurrence and negatively affects functional outcome in patients with TGCT of the hindfoot.